Antioxidant capacity of synovial fluid in the temporomandibular joint correlated with radiological morphology of temporomandibular disorders. Issue 2 (February 2015) - Ishimaru, Kyoko; Ohba, Seigo; Yoshimura, Hitoshi; Matsuda, Shinpei; Ishimaru, Jun-Ichi; Sano, Kazuo
Abstract We investigated the correlation between the antioxidant capacity of synovial fluid and radiological findings of intra-articular structures in patients with disorders of the temporomandibular joint (TMJ). We recruited 21 patients (9 men and 12 women, aged 18–84 years of age) with such disorders, excluding myofascial pain and dysfunction syndrome, or other muscular disorders. The clinical variables recorded included age, sex, interincisal distance, and visual analogue pain scores (VAS). Radiological findings were obtained from diagnostic arthrogram and cone-beam computed tomography (CT). The antioxidant capacity of the synovial fluid was measured by chemiluminescence. Eleven patients were radiologically diagnosed with closed lock, and the remaining 10 with no closed lock. An anchored intra-articular disc was most often seen on cone-beam CT (n = 19) followed by perforated disc (n = 7), osteoarthrosis (n = 7), and anterior disc displacement without reduction (n = 5). Although there were no significant differences between antioxidant capacity and age, sex, VAS, or any findings on cone-beam CT, antioxidant capacity was significantly decreased in the patients with closed lock compared with those who did not have closed lock (p = 0.02). The results suggest an association between the oxidative stress of the synovial fluid and closed-lock in disorders of the TMJ.